The Influence of Price, Service, and Product Quality on Interest in Buying Cattle at MJR Farm Boyolali - Nanda Nurul Umami; Triyanto Triyanto (International Journal of Business and Quality Research, 2025)
The purpose of this research is to determine how price, service quality, and product quality which are considered independent variables affect purchasing intent. Using the purposive sampling method, 42 respondents were chosen for the research sample. Questionnaires were used to gather data, which was then analyzed using multiple linear regression methods in SPSS version 26.0. Research instrument reliability and validity were confirmed by the results of the reliability and validity test. In addition, the regression model passes the traditional assumption test for normality, multicollinearity, and heteroscedasticity. The results of the hypothesis tests (t-test and F-test) and multiple linear regression analysis were as follows: (1) The quality of the service has a positive and substantial effect on the interest to buy. (2) The quality of the product also has a positive and significant effect on the interest to buy. At the same time, there is a statistically significant relationship between interest in purchasing and the three independent variables of price, service quality, and product quality. R2 shows that the model's independent variables can explain a large portion of the variance in purchase intent.